2004
DOI: 10.1177/0363546503262646
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Subclinical Medial Collateral Ligament Injury and Posteromedial Impingement in Professional Baseball Players

Abstract: This study demonstrates a high rate of abnormal magnetic resonance imaging findings in asymptomatic throwers' elbows. These baseline findings must be considered when magnetic resonance imaging is being used as a factor in treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 11 publications
2
62
0
Order By: Relevance
“…Asymptomatic elite-level throwers may have baseline progressive, adaptive changes in the UCL on imaging studies that may not correlate with the future risk of injuries. 21,24,25 Wright et al 41 used plain radiographs to examine a cohort of 56 asymptomatic professional baseball pitchers and found that degenerative changes developed over time, but these changes did not correlate to the time spent on the Major League Baseball disabled list or risk of future injuries. In addition, it is difficult for plain radio-graphs to accurately assess the structural integrity of the UCL or detect any associated soft tissue injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic elite-level throwers may have baseline progressive, adaptive changes in the UCL on imaging studies that may not correlate with the future risk of injuries. 21,24,25 Wright et al 41 used plain radiographs to examine a cohort of 56 asymptomatic professional baseball pitchers and found that degenerative changes developed over time, but these changes did not correlate to the time spent on the Major League Baseball disabled list or risk of future injuries. In addition, it is difficult for plain radio-graphs to accurately assess the structural integrity of the UCL or detect any associated soft tissue injuries.…”
Section: Discussionmentioning
confidence: 99%
“…6 All images were read by the same board-certified, fellowship-trained, musculoskeletal radiologist (N.S.M.) who was blinded to all participant data including the throwing limb.…”
Section: Methodsmentioning
confidence: 99%
“…The mechanism of ulnar collateral ligament injury involves forceful valgus stress during overhead throwing, medial stretching of the soft tissue, and posterior impingement [9,23]. The anterior bundle of the ulnar collateral ligament can be observed using high-resolution ultrasound.…”
Section: Ulnar Collateral Ligament Injurymentioning
confidence: 99%